CMHTs for older people: team managers' views surveyed. Issue 5 (9th December 2014) - Abendstern, Michele; Brand, Christian; Harrington, Val; Jasper, Rowan; Tucker, Sue; Wilberforce, Mark; Challis, David
Abstract : Purpose: – The purpose of this paper is to identify features of community mental health teams (CMHTs) for older people valued by their managers, and those they would most like to change. Design/methodology/approach: – Content analysis was used to analyse "free text" responses to open questions from a national survey about CMHTs' organisational structures and processes. Responses were sorted into statements which were categorised into content areas and higher level dimensions. Findings: – Free text information was provided by 376 teams (an 88 per cent response rate). Eight higher level dimensions were identified. One related specifically to integration with social care services, whilst several more included material about other aspects of intra-team integration (e.g. documentation and location). The largest proportion of statements related to staffing and teamwork. Statements about inter-personal and inter-professional issues were largely positive, whilst statements about resources, bureaucracy and integration with social care services typically detailed desired changes. Practical implications: – Four key issues emerged comprising a high level of support from managers to develop integrated practices; a need to define the focus of CMHTs for older people and to be fully resourced; and the importance of a nurturing and supportive team environment. Originality/value: – The methodology provides a bridge between qualitative and quantitative research, exploring the volume of statements on particular topics and their meaning.